Heat-killed Pseudomonas aeruginosa drives M1 polarization on BCG- primed macrophages - Rosa, Caio Pupin (2023)
Innate trained immunity is a recent concept regarding the training or tolerance acquired by macrophages, natural killer (NK) cells, dendritic cells and epithelial cells before heterologous stimulus. Given the novel data concerning macrophage training in pneumonia models and, thereby, the possibility of prevention and/or treatment of respiratory infections, this work aims to evaluate macrophage priming in vitro by BCG and/or HKPa. For this purpose, C57BL/6 mice bone-marrow-derived macrophages were plated and stimulated with BCG and/or HKPa. CD11b+ macrophage displayed activation through higher immunofluorescence of CD80/86, when homologous or heterologous stimulation occurred with BCG and/or HKPa. These cells also showed pro-oxidant status before BCG stimulus, through TBARS, TRAP and NADPH-oxidase tests. Nitric oxide concentration was augmented in BCG heterologous stimulation. Moreover, there was higher secretion of IL-6 when BCG heterologous stimulation occurred. However, homologous HKPa stimulation augmented IL-10 expression and secretion levels. Therefore, this study suggests that macrophages were primed by BCG, when there was heterologous stimulation with HKPa, and that homologous stimulation with HKPa induced immune tolerance.